Social Entrepreneurship Marketing Communication Strategy in Maintaining Customer Loyalty - Dewi Rachmawati; Taufan Teguh Akbari; Sandy Adithia (Communicare : Journal of Communication Studies, 2021)
Social entrepreneurship is a part of the world of entrepreneurship which is a combination of conventional profit-oriented businesses with a movement that is oriented towards social change. Social entrepreneurship has the potential as a solution that creates innovation, solves social problems, as well as creates new, better social values. However, its new existence and its form which is a combination of the two opposing values is a big challenge for these business actors. One way that can be a bridge to answer this problem is through the right marketing communication strategy not only to find the right customers, but also to create loyalty in order to create a sustainable business ecosystem. Therefore, this study was conducted to examine the form of marketing communication strategies of social entrepreneurs in order to find the right form of strategy in maintaining customer loyalty. The approach taken is a descriptive qualitative methodology with in-depth interviews with several resource persons who are the founders or leaders of start-up Social Entrepreneurs. The results showed that the strategies implemented by start-up social entrepreneurs including DuAnyam, Wangsa Jelita & Sunkrisps were very diverse and mostly through digital channels. From this channel, they concocted various ways to keep customers loyal and get benefits from the social entrepreneur program.